BRAND DEVELOPMENT STRATEGY OF MICRO SCALE SHOE INDUSTRIES BASED ON AUGMENTED REALITY FOR SMARTPHONE APPLICATION - Rendy Ridwan Hidayat; Andar Bagus Sriwarno (Jurnal Sosioteknologi, 2015)
One of the best fashion products made in Bandung is shoes. Bandung micro scale shoe industries have a great potential to reach international market. But it is still constrained by conventional product marketing. This research aims to explore digital information technology to develop digital product marketing. At this moment, digital marketing strategy has been able to reach the gaps that cannot be done through conventional strategy. This research focused on digital interaction development intended as a bridge for consumers to get product information through augmented reality. User can see the shape, material, and color closely resembling real shoes through augmented reality feature. This is the main solution offered in this research.Keywords: macro scale shoes, digital, marketing strategy, brand strategy, augmented realitySalah satu produk fesyen terbaik buatan Bandung adalah sepatu. Industri sepatu skala kecil memiliki potensi besar untuk menembus pasar internasional, tetapi masih terkendala pemasaran produk konvensional. Penelitian ini bertujuan untuk mengeksplorasi teknologi informasi digital untuk mengembangkan pemasaran produk digital. Pada saat ini, strategi pemasaran digital telah mampu menjembatani kesenjangan yang tidak dapat diatasi dengan strategi konvensional. Penelitian ini difokuskan pada pengembangan interaksi digital yang ditujukan sebagai jembatan bagi konsumen untuk mendapatkan informasi produk melalui augmented reality. Pengguna dapat melihat bentuk, bahan, dan warna yang sangat mirip dengan sepatu yang sebenarnya melalui fitur augmented reality, sebuah solusi penting yang ditawarkan dalam penelitian ini.Kata kunci: industri sepatu, sistem informasi digital, pemasaran produk, augmented reality